Assessment of Expression of SOCS Genes in Acquired Immune-Mediated Polyneuropathies - Taheri, Mohammad; Sangseifid, Somayeh; Shahani, Pariya; Eftekharian, Mohammad Mahdi; Arsang-Jang, Shahram; Ghafouri-Fard, Soudeh (Frontiers in Immunology, 2021)
Acquired immune-mediated polyneuropathies are classified to some subtypes among them are acute and chronic inflammatory demyelinating polyradiculoneuropathies (AIDP and CIDP). These two conditions share some common signs and underlying mechanisms. Based on the roles of Suppressor of cytokine signaling (SOCS) genes in the modulation of immune system reactions, these genes might be involved in the pathogenesis of these conditions. We evaluated expression of SOCS1-3 and SOCS5 genes in the leukocytes of 32 cases of CIDP, 19 cases of AIDP and 40 age- and sex-matched controls using real time PCR method. The Bayesian regression model was used to estimate differences in mean values of genes expressions between cases and control group. Expression levels of SOCS1 and SOCS2 were significantly lower in male patients compared with controls. This sex-specific pattern was also observed for SOCS3 down-regulation. Based on the area under curve values in Receiver Operating Characteristics (ROC) curve, diagnostic powers of SOCS1, SOCS2, SOCS3 and SOCS5 genes in the mentioned disorder were 0.61, 0.73, 0.68 and 0.58, respectively. Expression of none of genes was correlated with age of enrolled cases. The current study shows evidences for participation of SOCS genes in the pathophysiology of acquired immune-mediated polyneuropathies.